Naturalization in Sports from the Perspective of Sports Nationalism Based on Bhinneka Tunggal Ika - Prasetio, Dicky Eko (Badan Pembinaan Ideologi Pancasila, 2025)
Naturalization in sports is a global phenomenon that occurs worldwide, including in Indonesia. In Indonesia, this creates problems in the form of the stigma of